Determining the Price of Tuna Fish and Income of Tuna Fish Traders - Retno Sari, Nur Aidah Binti; Basuki, Ferry H.; Hehanussa, Solami J.; Sangadji, Maryam (Cita konsultindo, 2025)
Tuna is the main fishery commodity that has high economic value in Tial Village, Central Maluku. This research aims to analyze the factors that influence the determination of tuna prices and their impact on the income of tuna traders in the village. The approach used was qualitative research using in-depth interviews and direct observation of 10 tuna fish traders in the local market in Tial Village. The research results show that determining the price of tuna is influenced by several factors, such as demand and supply, operational costs, weather conditions, and government policies related to fisheries. In addition, frequent price fluctuations affect traders' income, which tends to be higher when tuna prices rise and lower when prices fall, although sales volumes may increase. Traders in Tial Village use flexible pricing strategies, adapting to market conditions and the costs they incur. This research concludes that the income of tuna traders is strongly influenced by price dynamics and other external factors, which makes the tuna fish trade in this village face major challenges.